Determinación de biomarcadores moleculares en leche y su posible aplicación en el diagnóstico y tratamiento de la mastitis bovina - Caggiano N. (2016)
Mastitis is a disease with increased morbidity and mortality within dairy herds, seriously affecting milk production and milk quality. That's why in this work the activity of Metalloproteinase 2 and 9, from milk of cows and heifers with subclinical and clinical mastitis and in healthy animals was evaluated. Total protein fractions and different caseinolytic activity were also evaluated. The activity of Metalloproteinase 2 and 9 was assessed by zymography as caseinolytic activity and total protein fractions by SDS-PAGE. The results showed a large increase in the activity of Metalloproteinase 2 and 9 in clinical mastitis compared with subclinical and healthy animals, these results were not significant due to the large standard deviation due to the large variability among pathogens within the groups. Significant differences were found between the group Streptococcus spp. and sub-clinical and healthy groups in terms of total caseinolytic activity (p <0.05), and significant differences were observed in terms of total casein in the same groups (p <0.01).